2015
DOI: 10.1016/j.jaut.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome profiling reveals significant DNA demethylation of interferon signature genes in lupus neutrophils

Abstract: Recent evidence suggests that neutrophils play an important role in the pathogenesis of lupus. The goal of this study was to characterize the epigenetic architecture, by studying the DNA methylome, of neutrophils and low density granulocytes (LDGs) in lupus patients. We studied 15 lupus patients and 15 healthy age, sex, and ethnicity matched controls. Genome-wide DNA methylation was assessed using the Illumina HumanMethylation 450 BeadChip array, which includes over 485,000 methylation sites across the entire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 28 publications
15
119
0
2
Order By: Relevance
“…All of the differentially methylated CpGs in IFI44L were located within 1500 base-pairs upstream of the transcription start site and the 5′-untranslated region, including cg00855901, cg03607951, cg06872964, cg17980508, cg13304609 and cg05696877 (see online supplementary table S4), among which cg06872964 is one of very significant differentially methylated CpG sites comparing patients with SLE with HCs (Δβ SLEa vs HC =−0.31 and Δβ SLEi vs HC =−0.30) (see online supplementary figure S1). In addition, our previous studies have revealed significant hypomethylation of the IFI44L promoter in naive CD4 + T cells and neutrophils of patients with SLE compared with HCs 19 21. Therefore, we assessed the diagnostic value of IFI44L promoter methylation level in SLE using peripheral blood samples.…”
Section: Resultsmentioning
confidence: 96%
“…All of the differentially methylated CpGs in IFI44L were located within 1500 base-pairs upstream of the transcription start site and the 5′-untranslated region, including cg00855901, cg03607951, cg06872964, cg17980508, cg13304609 and cg05696877 (see online supplementary table S4), among which cg06872964 is one of very significant differentially methylated CpG sites comparing patients with SLE with HCs (Δβ SLEa vs HC =−0.31 and Δβ SLEi vs HC =−0.30) (see online supplementary figure S1). In addition, our previous studies have revealed significant hypomethylation of the IFI44L promoter in naive CD4 + T cells and neutrophils of patients with SLE compared with HCs 19 21. Therefore, we assessed the diagnostic value of IFI44L promoter methylation level in SLE using peripheral blood samples.…”
Section: Resultsmentioning
confidence: 96%
“…23 Thus, this evidence supports an inducible epigenetic and genetic regulation of neutrophil gene expression. Moreover, the association between genetic variants 24 and altered methylation profiles 25 in neutrophils associated with disease susceptibility emphasizes the importance of understanding how gene expression is controlled in neutrophils.…”
Section: Transcriptional Plasticity: Numbers Mattermentioning
confidence: 99%
“…The authors found that the highest DNA methylation variation lay in gene body and upstream regions, whereas the lowest was observed in promoters. The iVMFs were mainly associated with tran- Kaplan et al, 2004Javierre and Richardson, 2011Lu et al, 2007Oelke et al, 2004Lu et al, 2002Coit et al, 2013Zhao et al, 2010bHedrich et al, 2014 B cells CD5 HRES1 hypomethylation increased B cell activation induction of cross-reactive autoantibodies Garaud et al, 2009Fali et al, 2014 PBMCs IFNGR2 LCN2 hypomethylation lymphadenopathy and kidney damage a common marker for lupus nephritis Schwarting et al, 1998;Javierre et al, 2010Javierre et al, 2010 Whole blood IFI44L a highly specific and sensitive biomarker Zhao et al, 2016b Neutrophils MX1, IFI44L, IFITM1, PARP9, IFIT3, DDX60, LY6E, ISG15 hypomethylation increased production of type I IFN driving abnormal B cell differentiation Coit et al, 2015b Zhan/Guo/Lu scription regulation, responsive function, and signal transduction pathways, and positively correlated with inclusion of the exon when found at differentially expressed exons. Neutrophils are also found to play an important role in the pathogenesis of lupus.…”
Section: Dna Methylation/demethylationmentioning
confidence: 99%
“…Neutrophils are also found to play an important role in the pathogenesis of lupus. Coit et al [2015b] recently performed an epigenome-wide study between lupus patients and controls and identified 293 differentially methylated CG sites in neutrophils, of which the majority (68%) were hypomethylated. Among the differentially methylated sites, IFN signature genes were found demethylated in a robust and consistent way in lupus neutrophils compared to controls ( table 1 ), suggesting a pathogenic role for neutrophils in lupus.…”
Section: Dna Methylation/demethylationmentioning
confidence: 99%